(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
When people are physically separated, such as during the COVID-19 pandemic, they are more likely to use digital communication to replace in-person interactions. However, the persistence of digital inequality suggests that, during a public health crisis, not everyone will be equally capable or inclined to increase digital communication. The purpose of this study is to be able to choose the best form of communication to employ in daily interactions, meetings at work, and interpersonal interactions, as well as how it benefits us. Nowadays, many people use digital communication because it is easier and faster, but our studies show that the use of physical communication is better than digital communication because it is clearer and avoids wrongly gathering information.